Managing communication and participation in Canary Island firms - Acosta-Rubio, Z.; Febles-Acosta, J.; Banaitis, A.; Ferreira, F. (E+M. Ekonomie A Management, 2022)
Business organizations and management encompass a wide range of aspects requiring research and analysis. Two key issues are communications management and employee participation promotion within firms. This study focused on the variables of communication and participation in organizational structure, business decision making, transmission of orders, supervision, and control in small and micro-enterprises in the Canary Islands, Spain. The research examined the two variables’ ability to generate increased involvement in and employee identification with their firm. The analytical framework applied sought to investigate Canarian managers’ criteria and priorities regarding using communication and participation as management tools. The methodology included the Rasch analysis technique. The study analyses seven variables considered relevant in relation to communication that are communication between management and workers, fluid and informal communication, use of information technology in internal communication, access of all workers to new information technology, linking/relationship systems between units of the same level, linking/relationship systems between units of different levels and the existence of information disseminated as a tool. Likewise, among the variables related to participation, twelve variables recognized as relevant in the literature are analysed. These variables are setting specific objectives for workers, individual initiative, cooperation, decentralization of decision making, control, participation in decision making, participation in setting objectives, workers’ autonomy in decision making when carrying out their work, initiative in their work, control of their work, commitment and involvement of managers in daily work and delegation of authority to lower levels. The predominance of small businesses, in many cases managed by their owners, allows us to appreciate a vertical communication based on direct supervision, from top to bottom. The results reveal a poorly balanced combination of communication and participation systems in Canarian firms. These marked imbalances have consequences for managers’ coordination mechanisms and potential for effectively managing their firms.